Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13045-017-0492-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of epigenetics-microRNA axis in drug resistance of multiple myeloma

Abstract: Despite administration of novel therapies, multiple myeloma (MM) remains incurable with resistance to drugs leading to relapse in most patients. Thus, it is critical to understand the detailed mechanisms underlying the drug resistance of MM and develop more effective therapeutic strategies. Genetic abnormalities are well known to play a central role in MM pathogenesis and therapy resistance; however, epigenetic aberrations mainly affecting the patterns of DNA methylation/histone modifications of genes (especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 91 publications
(83 reference statements)
0
37
0
Order By: Relevance
“…miRNA plays a role in regulating gene transcription by inhibiting or degrading target mRNA. 34,35 miRNA-125 is a kind of miRNA involved in tumorigenesis and development, including miR-125a, miR-125b-1, and miR-125b-2, and has the effect of oncogene or tumor-suppressor gene. 32,33 In addition, it has been found that the abnormal expression of miRNA may be associated to the proliferation, F I G U R E 3 Identification of USP5 as the target gene of miR-125a in MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA plays a role in regulating gene transcription by inhibiting or degrading target mRNA. 34,35 miRNA-125 is a kind of miRNA involved in tumorigenesis and development, including miR-125a, miR-125b-1, and miR-125b-2, and has the effect of oncogene or tumor-suppressor gene. 32,33 In addition, it has been found that the abnormal expression of miRNA may be associated to the proliferation, F I G U R E 3 Identification of USP5 as the target gene of miR-125a in MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the clinical heterogeneity of MM is thought to arise from multiple genomic events that result in tumor development and progression 2. These include genetic and epigenetic alterations, including point mutations, translocations (eg, t(4;14) and t(14;16)), deletions (eg, del(17p)),3 aberrant DNA and histone methylation,4 and/or abnormal microRNA expression 5…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al found that KIAA0495, an lncRNA transcribed from chromosome 1p36, was progressively downregulated from normal plasma cells to monoclonal gammopathy of undetermined significance (MGUS) and to symptomatic myeloma by gene expression profiling . DNA methylation has been implicated in the pathogenesis and prognosis of MM . However, the methylation of KIAA0495, which leads to the reversible silencing of KIAA0495 expression in MM, has been rarely detected in primary samples of MM at diagnosis or relapse.…”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%
“…38 DNA methylation has been implicated in the pathogenesis and prognosis of MM. 39 However, the methylation of KIAA0495, which leads to the reversible silencing of KIAA0495 expression in MM, has been rarely detected in primary samples of MM at diagnosis or relapse. This means that it may not be associated with its progressive downregulation in cells from normal plasma cells to MGUS and to MM.…”
Section: Kiaa0495mentioning
confidence: 99%